1972
DOI: 10.1042/bj1281033
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mammalian mitochondrial ribosomal ribonucleic acid from different species

Abstract: Mitochondrial ribosomal RNA species from mouse L cells, rat liver, rat hepatoma, hamster BHK-21 cells and human KB cells were examined by electrophoresis on polyacrylamide-agarose gels and sedimentation in sucrose density gradients. The S(E) (electrophoretic mobility) and S values of mitochondrial rRNA of all species were highly dependent on temperature and ionic strength of the medium; the S(E) values increased and the S values decreased with an increase in temperature at a low ionic strength. At an ionic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1973
1973
1978
1978

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The values for their electrophoretic mobilities and the equivalent sedimentation coefficients were respectively 20.5 Se and 19.5S, 16.3S, and 16.2S, and 15.4S, and 13.8S. The differences for each RNA species between the S and S. values may represent conformational changes due to the influence of the lower ionic strength used in polyacrylamide-gel electrophoresis (Groot et al, 1970;Mitra et al, 1972).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The values for their electrophoretic mobilities and the equivalent sedimentation coefficients were respectively 20.5 Se and 19.5S, 16.3S, and 16.2S, and 15.4S, and 13.8S. The differences for each RNA species between the S and S. values may represent conformational changes due to the influence of the lower ionic strength used in polyacrylamide-gel electrophoresis (Groot et al, 1970;Mitra et al, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…Rounding off the Se, values to 20 and 15 respectively, they are nearly identical with the values reported by Groot et al (1970) and Bartoov et al (1970) for rat liver mitochondrial RNA, and something similar occurs with our 15 and 14S values when compared with the 16 and 13S peaks obtained by the same authors. Groot et al (1970) and Mitra et al (1972) showed that the discrepancy between the S and S, values of the larger RNA in rat liver were due simply to conformational changes occurring during electrophoresis, and which were evident by carrying out the runs at different temperatures and ionic strengths. In the case of Walker carcinoma this explanation cannot account either for the presence of both 20 and 16S.…”
Section: Discussionmentioning
confidence: 99%